Psikoterapi Transpersonal Psikosintesis untuk meningkatkan kesejahteraan psikologis ibu dengan anak autisme - Sari, Amelia; Prabowo, Hendro (Universitas Muhammadiyah Malang, 2024)
Mothers of autistic children often experience psychological well-being problems, such as stress, anxiety, and depression, due to high demands for care and attention. This study aims to prove whether psychosynthesis intervention is effective in improving the psychological well-being of mothers with autistic children. The research method used in this study is a single case experiment with ABA design. The subject in this study is a mother who has an autistic child. Data collection was carried out by means of interviews, observation and ﬁlling out scales in the initial baseline phase (A), intervention phase (B) and ﬁnal baseline phase (A), and follow-up. The scale used is the Psychological Wellbeing scale. Data analysis techniques using visual inspection and Wilcoxon test. The results of the study with visual analysis showed that the Transpersonal Psychosynthesis Psychotherapy intervention was effective in improving the psychological well-being of mothers with children with autism, while the results of the Wilcoxon test obtained Z= -3,360 (p<0,01), which means that there is an effect of psychosynthesis to improve psychological well-being in mothers with children with autism.